Evaluation of the performance of health regions in the State of Rio de Janeiro (Research, Society and Development, 2020)
This study aims to evaluate the performance of public health expenditure indicators in the nine Health Regions of the State of Rio de Janeiro. Data from the Public Health Budget Information System (SIOPS), in the public domain, involving the nine Health Regions of the State of Rio de Janeiro, with annual periodicity between 2007 and 2016, adjusted by the National Broad Consumer Price Index (IPCA), were extracted. Then, the data were analyzed through descriptive statistics and presented in the form of table and graph. The data showed that metropolitan regions I and II have been maintaining their total expenditures and declining per inhabitant in recent years. In contrast, the RS of the Coastal Lowland, Ilha Grande Bay and North have their expenses increasing, and it is last, the differences reach results considered pronouncedly high. These RS enjoy increases in their revenues from incentives from oil and gas production or state environmental tax incentives. It is considered that despite the high health expenses of the three RS compared to the metropolitan health regions, it cannot be inferred that the quality of the production processes and health products of the latter are worse, because the human development rates are higher in these health regions than in the RS of higher health expenditures in the period studied.